Item Analysis of the G-Form Questionnaire on Students’ Motivation for Online Learning - Putie Maharani Basa (Indonesian Journal of Advanced Research, 2026)
Technological advancements have led to the emergence of various online learning platforms and media as part of the innovation inherent in that technology. Online learning is a process that takes place online, being both open and massive, thereby enabling broader participation. In this context, both intrinsic and extrinsic motivations simultaneously influence students' academic performance. This study analyzes test items distributed via Google Forms to 100 students organized into 10 groups regarding their learning motivation in the context of online learning. The analysis employs methods assessing discrimination power, difficulty level, motivation, and validity. The analysis concludes that all 15 test items are valid. Specifically, six items are recommended for use, four require revision, and five must be replaced, particularly given that the items are distributed via Google Forms—to enhance student motivation to complete them.